Nonconvulsive Status Epilepticus Resembling Clinical Absence with Atypical EEG Pattern - Channaiah Srikanth Mysore; Najib Murr; Rana Zabad; John Bertoni (Case Reports in Neurological Medicine)
Objective. We are reporting two cases: a patient with steroid responsive encephalopathy associated with autoimmune thyroiditis (SREAT) and another patient with secondary progressive multiple sclerosis (SPMS), both presenting with altered mental status (AMS) and later diagnosed with nonconvulsive atypical absence status epilepticus (AS), with atypical EEG changes. Methods. A report of two cases. Results. A patient with history of SREAT and the other with SPMS had multiple admissions due to AMS. For both, EEG revealed the presence of a high voltage generalized sharply contoured theta activity. A diagnosis of NCSE with clinical features of AS was made based on both clinical and EEG features. There was significant clinical and electrographic improvement with administration of levetiracetam for both patients in addition to sodium valproate and Solumedrol for the SREAT patient. Both patients continued to be seizure free on follow-up few months later. Conclusions. This is a report of two cases of atypical AS, with atypical EEG, in patients with different neurological conditions. Prompt clinical and EEG recovery occurred following appropriate medical treatment. We think that this condition might be underreported and could significantly benefit from prompt treatment when appropriately diagnosed.